Key aspects and consequences of Rafael Correa´s left-wing rule in Ecuador - Medina González Vinicio Xavier (Ибероамериканские тетради)
The article analyzes the main directions of political radicalism inEcuador, in particular the “left turn” of the Ecuadorian government led by R. Correa. It is proved that the new geopolitical situation in the modern world has led to changes in the political and economic strategy of Latin America, when one of the leading political and ideological trends in recent times in the region has become the “left turn” of a number of Latin American governments, which emerged as an alternative direction in search of achieving social equality and improving the economic situation. The article explores the goal of radical socio-economic transformations inEcuadorin 2007, their main tasks and consequences. An analysis of the key achievements of the government of the “civil revolution” R. Correa is made, their negative consequences are revealed, the analysis of the main effects of radical reforms affecting the political, economic and social situation in Ecuador is carried out. It was revealed that in foreign policy the main tasks forEcuadorwere to reduce dependence on theUnited States, eliminate geopolitical isolation from Europe andAsia, and diversify international relations.